Peningkatan Kemampuan Berpikir Kritis Siswa Melalui Model Problem Based Learning Pada Pembelajaran IPAS Kelas V SD Berbantuan Media Augmented Reality - Uliyanti, Ilana Anggita; Ardianti, Sekar Dwi; Fakhriyah, Fina (LPPM Institut Pendidikan Nusantara Global, 2024)
This research aims to describe the application of the Problem Based Learning model using Augmented Reality media to improve critical thinking skills, student activities and teachers' teaching skills in science learning. This classroom action research was carried out in 2 cycles in class V of SD 1 Kaliwungu Kudus with research subjects totaling 26 students. Data collection techniques use observation, interviews, documentation, tests. Data analysis techniques are descriptive qualitative and descriptive quantitative. The results of this research were that teachers' teaching skills improved in cycle I, obtaining a score of 54.16 with sufficient qualifications and increased in cycle II with a score of 81.94 with good qualifications. Student activity increased in the first cycle, the attitude aspect was obtained with a score of 55.39, sufficient qualifications and in the second cycle, the score was 78.48 with good qualifications. Student activities in the skills aspect of cycle I obtained a score of 57.70, sufficient qualifications, then increased in cycle II by obtaining a score of 77.49, good qualifications. The results of the students' critical thinking ability test in cycle I obtained classical completeness of 46% and increased in cycle II with classical completeness reaching 80%. It can be concluded that the application of the Problem Based Learning learning model in science and science learning assisted by Augmented Reality media can improve teacher teaching skills, student learning activities, and critical thinking abilities of class V students at SD 1 Kaliwungu Kudus.